Development and Characterization of Modified Chitosan Lipopolyplex for an Effective siRNA Delivery - Supe, Shibani; Upadhya, Archana; Dighe, Vikas; Singh, Kavita (AAPS PharmSciTech, 2024)
Cytotoxicity, speedy degradation, and limited cellular absorption are the foremost features influencing the successful delivery of RNAs. Chitosan (Cs) is a polymer that offers an advantage due to its bio-compatibility and biodegradable nature, making it an ideal polycationic vector for delivering siRNA. In this study, chitosan has been modified with arginine in order to increase its encapsulation of siRNA and improve cellular absorption. It was discovered that arginine and guanidino moieties could transport through membranes of cells and play an important part in membrane permeability. FTIR and 13 C NMR were used to characterize the complex. These chitosan-arginine (CsAr) siRNA complexes are further encapsulated in anionic DPPC/cholesterol liposomes to combine the effects of liposome-chitosan-arginine complexes called lipopolyplexes (LCAr). Formed LCAr were investigated for their lipid/CsAr-siRNA ratios, size, zeta-potential, heparin, and serum RNase stability by agarose gel retardation, and cell uptake efficiency compared to their “parent” polyplexes. Results revealed complete lipidation of CsAr-siRNA polyplexes at lipid mass ratio 10 resulting in lipopolyplexes in the 120 to 230nm range. Polyplex entrapped ~70% of siRNA, whereas lipidation increases siRNA encapsulation to ~95%. Developed LCAr showed ~4 times less hemolytic potential as compared to the parent polyplexes at the highest siRNA dose. The CsAr-siRNA and its lipid-coated form showed enhanced cellular association as compared to the marketed Lipofectamine 2000 proving its effectiveness in siRNA delivery. CsAr-liposome conjugation is simple and safe, and serves as a robust carrier for gene transport in physiological situations without compromising transfection efficacy. Graphical Abstract